PROSES PENGEMBANGAN KETERAMPILAN MEMBACA PEMAHAMAN (READING COMPREHENSION) MAHASISWA - Bambang Sulistyo (Jurnal Semantik, 2013)
In reading comprehension depends on three factors. The first factor is that the reader understand the text structure. The second factor is that the reader can perform metacognitive control over the content being read. This means that the reader is able to monitor and reflect on the level of comprehension when reading the material. The third and most important criteria, which affect the understanding is that the reader has sufficient background to the content of the text and vocabulary are presented Tankersley (90-91). Good readers in reading comprehension, will be actively involved and thought processes. Good readers during the reading process will find connections between background knowledge with new information in the text. Readers sift relevant new information or that are not relevant to their background knowledge which is astorehouse of information and life experiences.Kata Kunci: Membaca Pemahaman, Literasi, Pengetahuan Latar, Metakognitif